Endogenous Salicylic acid Estimation in Wheat leaves treated with Salicylic acid and infected with Alternaria triticina - El-Alwany, Abdalla M.; Banni, Abdel-Hakim S. (Al-Mukhtar Journal of Sciences, 2023)
This study was aime to measure the accumulation of endogenous salicylic acid, as indicator for systemic acquired re-sistance of wheat plants of “Utique” variety. The plant was sprayed with salicylic acid (SA) or water as control, at the five-leaf stage, later infected with leaf blight caused by Alternaria triticina. Leaf samples were removed after 10, 20, and 30 days of inoculation to test their endogenous content of salicylic acid as it is the primary internal signal indicating the emergence of systemic acquired resistance in plants, by the spectrophotometer measuring. Endogenous SA values were ascending dramatically from 10 days to 20 days and maximum with 30th day significantly, while control plants exhibit lower values in all day periods, insignificantly. SA treatments proved reduction in disease incidence after 10 days with 54% and after 20 days with 64%, while after 30 days the reduction recorded high percentage of 80%. In comparison between the time intervals, disease severity was clearly reduction and reached to 83% after 10 days of inoculation then decreased to 72% for both 20th and maintained its stability on the 30th day of inoculation by 72%. This study was proved the reduction of wheat leaf blight incidence and disease severity as a result of treatment by using 1Millimolar (mM) of SA was leading to accumulation of significant levels of endogenous SA as indicator for internal induced resistance in plant.